The Change Management in the Development of Pesantren-Based Curriculum Integration - Lestari, Wiji Dewi; Sulton, Ahmad (Pascasarjana IAIN Kudus, 2025)
This study explores change management in the development of the pesantren-based curriculum at MI Tahfizh Al-Furqon Ponorogo. The study employs a qualitative approach with a case study model. Observations, interviews, and documentation were used to collect data for this study. This study used the interactive data analysis model developed by Miles, Huberman, and Saldana, which includes collection, condensation, presentation, and conclusion-drawing. The study found that the change management planning for the pesantren-based curriculum integration development at MI Tahfizh Al-Furqon utilizes situational diagnostics. Implementing change management in pesantren-based curriculum integration at MI Tahfizh Al-Furqon involves three core activities: communicating changes, determining curriculum models, and blending curriculum concepts. The implementation was evaluated through coordination and field surveys. This study contributes to the practical understanding of how change management strategies can effectively be applied in pesantren education, particularly in developing curricula that incorporate pesantren values while meeting modern educational demands.